2021
DOI: 10.1002/ana.26066
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Mapping of Ripple Onset Predicts Outcome in Epilepsy Surgery

Abstract: Objective: Intracranial electroencephalographic (icEEG) studies show that interictal ripples propagate across the brain of children with medically refractory epilepsy (MRE), and the onset of this propagation (ripple onset zone [ROZ]) estimates the epileptogenic zone. It is still unknown whether we can map this propagation noninvasively. The goal of this study is to map ripples (ripple zone [RZ]) and their propagation onset (ROZ) using high-density EEG (HD-EEG) and magnetoencephalography (MEG), and to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Among others, our group has shown that HFOs are promising interictal biomarkers of epilepsy, which can be recorded non-invasively with scalp EEG and MEG (Papadelis et al, 2009(Papadelis et al, , 2016Tamilia et al, 2017;Zijlmans et al, 2017;Thomschewski et al, 2019;Thomschewski et al, 2021). Surgical resection of the non-invasively identified HFO-zone predicts surgical outcome (Tamilia et al, 2021). Here, we localized an incident of HFO-activity observed in both conv-EEG and MEG and localized with MSI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among others, our group has shown that HFOs are promising interictal biomarkers of epilepsy, which can be recorded non-invasively with scalp EEG and MEG (Papadelis et al, 2009(Papadelis et al, , 2016Tamilia et al, 2017;Zijlmans et al, 2017;Thomschewski et al, 2019;Thomschewski et al, 2021). Surgical resection of the non-invasively identified HFO-zone predicts surgical outcome (Tamilia et al, 2021). Here, we localized an incident of HFO-activity observed in both conv-EEG and MEG and localized with MSI.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent review paper, Zijlmans et al (2019) proposed the use of electric and magnetic source imaging (ESI/MSI) obtained from high-density EEG (HD-EEG) or magnetoencephalography (MEG) for almost all electroclinical syndromes. Their proposal was based on findings from several research groups, including ours, showing that ESI and MSI can provide valuable clinical information in the presurgical evaluation of patients with DRE, evaluated for surgical therapy (Mégevand et al, 2014;Papadelis et al, 2016;Tamilia et al, 2017Tamilia et al, , 2019Tamilia et al, , 2020Tamilia et al, , 2021Plummer et al, 2019;Rampp et al, 2019;Ntolkeras et al, 2021;Papadelis and Perry, 2021;Ricci et al, 2021). ESI and MSI can provide a precise estimate of the irritative zone that can be interpreted as presurgical indicator of the EZ location (Tamilia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We must also mention that non-invasive recording techniques with a higher number of sensors [ 56 ], such as high-density EEG (>64 channels) or MEG [ 47 , 57 ], allow a more precise reconstruction of the network through smaller ROIs (also called virtual sensors). Most clinics still lack the equipment or resources to perform MEG or EEG monitoring with >64 electrodes: thus, while our proposed approach can be significantly enhanced in terms of localizing value, it paves the way for an easily implementable approach in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Source space was constrained to the cortex, which was composed of ~15,000 vertices per patient. We used a linearly constrained minimum variance (LCMV) beamformer to estimate brain activity within the source space [ 47 ]. Data covariance was computed from the EEG epochs, whereas identity matrix was used for noise covariance.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has also been suggested that HFOs sites are functionally connected which may be important in predicting response to epilepsy surgery [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%